Market segmentation in two-sided markets: TV rights for Premier League - Hans Jarle Kind; Lars Sørgard (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes market segmentation in a two-sided market that consists of media consumers and advertisers. The analysis is motivated by a European Court of Justice Decision in October 2011, which allowed viewers to take advantage of international price differences and buy access to Premier League TV matches from whichever country they like. We compare complete market segmentation with the new situation where consumers can purchase from abroad (allowing for passive sales). Clearly, such a change is likely to harm Premier League, which at present is sold at different prices to viewers in different countries. More surprisingly, we find that all viewers - including those that switch to purchasing from abroad - might also be harmed. We further show that the two-sidedness of the market may break down in the country that attracts foreign viewers.
Keywords: D43; K21; L13; 330; market segmentation; two-sided market; price discrimination; media market; passive sales; Fernsehprogramm; Fußballsport; Lizenz; Preisdifferenzierung; Marktsegmentierung; Medienökonomik; Theorie; Europa